Investigation on mechanical properties of glass fiber reinforced polyamide 6-polypropylene composites under different operating conditions - Nurizzathanis, Mohamad Kusaseh (2020)
Fiber reinforced polymers possess good properties such as light-weight, high levels of stiffness, high strength-to-weight ratio, and outstanding endurance strength as compared to other most common metallic alloys. This research study is investigating on mechanical properties of glass fiber reinforced polyamide 6-polypropylene composites under different operating conditions. Commonly only one type of matrix and one type of fiber are used to produce composites but this combination cannot meet the current needs in the production of polymer composite-based products that require better products in terms of their properties and capabilities. Thus, two matrices of polyamide 6 and polypropylene are combined and reinforced with glass fiber to produce new properties of a composite that have high strength of ductile materials. Five different dog-bone-shaped specimens of glass fiber reinforced polyamide 6-polypropylene composites were prepared; 70%PA6+30%PP polymer blend, 65%PA6+30%PP+5%GF composite, 60%PA6+30%PP+10%GF composite, 55%PA6+30%PP+15%GF composite, and 50%PA6+30%PP+20%GF composite. The research of glass fiber reinforced polyamide 6-polypropylene composites would differ from other researchers as there are 3 different categories of mechanical tests with different mechanical operating conditions performed for this research. The influence of different compositions of glass fiber reinforced PA6-PP composites was investigated with tensile, flexural, and impact tests under different loading conditions which is from a low rate to a high rate. Different strain rates are used for tensile tests with a low strain rate of 2 mm/min, medium strain rate of 6 mm/min, and high strain rate of 10 mm/min. For flexural tests, two different tension rates are used which are a low strain rate of 2 mm/min and a high strain rate of 4 mm/min and two different torques were used in impact tests which are 4 N.m and 5 N.m. Tensile properties of 70%PA6+30%PP polymer blend show low tensile modulus and tensile strength but at 50%PA6+30%PP+20%GF composite show an increased result even at different strain rates. The PA6-PP polymer blend show a ductile behavior if compare to PA6-PP-GF composite with 20%GF that show brittle behavior composites. A stress-strain graph of 50%PA6+30%PP+20%GF composite under strain rate of 10 mm/min tensile test shows a little elongation ability before fracturing compared to other PA6-PP-GF composites due to the high strain rate applied and also because of the brittle behavior of composites itself. Flexural properties of glass fiber reinforced PA6-PP composites show continuously increased properties as the glass fiber content is increased. Tensile and flexural properties show continuously increased results with the increase of glass fiber content as the strain rates increased. The flexural strength result of glass fiber reinforced PA6-PP composites at a strain rate of 4 mm/min is higher than a strain rate of 2 mm/min. The flexural strength of glass fiber reinforced PA6-PP composites at a strain rate of 2 mm/min also shows a higher strength than tensile strength results at 2 mm/min strain rate. Tensile and flexural test results show continuously improved results with glass fiber content increases. Moreover, the impact strength shows the higher result at 70%PA6+30%PP polymer blend but drastically decreased at 65%PA6+30%PP+5%GF composites. Then, the impact strength slightly increased when the glass fiber content up to 10% and 15% but when the glass fiber content is up to 20%, the impact strength is decreased again because of high glass fiber content absorbs less energy compared to a neat polymer blend. The mechanical properties of PA6-PP-GF composites are influenced by the different composition of glass fiber. The microstructure analysis of PA6-PP-GF composites revealed a long to short fiber pull-out as the strain rates applied vi for tensile properties is high and also showed a good interfacial bonding between glass fibers and PA6-PP matrices. The mechanical properties of the PA6-PP-GF composites can contribute to industrial applications such as inlets or intake manifolds in automotive parts, automotive bumpers to absorb impact energy if happens any collision, automotive valves, and other academic research in the future.